Adsorption of Heavy Metal Cr (VI) Using BioSorbent of Tea Dregs: Experimental and Modeling - . Mariana; . Mahidin; Farid Mulana (Syiah Kuala University, 2015)
Tea plants have been generally known by most of Indonesian as a refreshing drink. Tea leavesusually contain caffeine of 1-4%, tannins of 7-20% and a little essential oil. Powder of tea dregs has the ability to absorb heavy metal of chromium. The research objective was to study the adsorption kinetics of heavy metal ions of Cr (VI) using powder of tea dregs and to study factors that affect adsorption process of chromium metal. The analysis of sample solution concentration of Cr (VI) in this study was using Atomic Absorption Spectrophotometer (AAS). The effect of various process variables such as initial concentration of the metal solution, stirrer speed and concentration of modifying agent of sulphuric acid has been investigated. The results showed that the optimum adsorption process was obtained at adsorbate concentration of 125 ppm with activation process at sulphuric acid concentration of 0.8 M. The highest efficiency of heavy metal adsorption reached 83.24% with adsorption capacity of 5.202925 mg/g bio-sorbent. This adsorption was in accordance with the Langmuir Isotherm models with R2 value of 0.909. This study was also in accordance with kinetics of a second pseudo order with a R2 value of 0.997 and K of 0.752 g/mg. Minute